Introducing an aflatoxin-safe labeling program in complex food supply chains: Evidence from a choice experiment in Nigeria. (July 2021) - Sanou, Awa; Liverpool-Tasie, Lenis Saweda O.; Caputo, Vincenzina; Kerr, John
Highlights: Aflatoxin contamination is a key food safety issue in developing countries. Introducing aflatoxin-safe certification can elevate food safety standards. Economic agents in the midstream of value chains play an important role in food safety. Traders' WTP for aflatoxin certification depends on their buyers preferences. Traders selling to large feed and food companies and other traders care the most. Abstract: Food contaminated with aflatoxins is one of the more prominent food safety issues facing developing countries. These toxins impose an immense burden on countries that have to deal with the repercussions of the contamination. Repercussions include increased public health concerns, increased health care expenditures, and other economic tolls. To alleviate these food safety concerns, the implementation of aflatoxin-safe certification can potentially incentivize and elevate food safety standards. This study uses a discrete choice experiment approach to assess if traders are willing to pay a price premium for aflatoxin-safe maize and whether such a premium varies across their market channels. Results indicate that maize traders who sell to other traders, large feed mills, food companies, and retailers exhibit a higher willingness to pay (WTP) for aflatoxin-safe certification compared to those who sell to small feed mills and consumers. Relevant policy implications are discussed.